2015
DOI: 10.1371/journal.pone.0129485
|View full text |Cite
|
Sign up to set email alerts
|

TNFα Amplifies DNaseI Expression in Renal Tubular Cells while IL-1β Promotes Nuclear DNaseI Translocation in an Endonuclease-Inactive Form

Abstract: We have demonstrated that the renal endonuclease DNaseI is up-regulated in mesangial nephritis while down-regulated during progression of the disease. To determine the basis for these reciprocal DNaseI expression profiles we analyse processes accounting for an early increase in renal DNaseI expression. Main hypotheses were that i. the mesangial inflammation and secreted pro-inflammatory cytokines directly increase DNaseI protein expression in tubular cells, ii. the anti-apoptotic protein tumor necrosis factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 53 publications
2
16
1
Order By: Relevance
“…Interestingly, the localization of renal DNase I in humans with class IV lupus nephritis is mostly in the nuclei of tubular cells. Previously we have found that DNase I in nuclei of human renal proximal tubule epithelial cells is enzymatically inactive, and may possess another function besides the endonucleolytic role [28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the localization of renal DNase I in humans with class IV lupus nephritis is mostly in the nuclei of tubular cells. Previously we have found that DNase I in nuclei of human renal proximal tubule epithelial cells is enzymatically inactive, and may possess another function besides the endonucleolytic role [28].…”
Section: Discussionmentioning
confidence: 99%
“…During a longitudinal study on expression profiles in (NZBxNZW)F1 (BW) mice, we observed a tendency for DNase I up-regulation during mesangial nephritis, before a subsequent and distinct down-regulation of the gene during progressive disease (Fenton et al, 2009 ; Seredkina and Rekvig, 2011 ). In addition, we have observed nuclear localization of renal DNase I in tubular cells in human lupus nephritis (Thiyagarajan et al, 2015 ). Studies on cultured human renal proximal tubular epithelial cells (RPTEC) have also shown translocation of DNase I into the nucleus under certain conditions (Thiyagarajan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 89%
“…In addition, we have observed nuclear localization of renal DNase I in tubular cells in human lupus nephritis (Thiyagarajan et al, 2015 ). Studies on cultured human renal proximal tubular epithelial cells (RPTEC) have also shown translocation of DNase I into the nucleus under certain conditions (Thiyagarajan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations